A review on biomass-derived levulinic acid for application in drug synthesis. (17th February 2022) - Zhang, Mingyue; Wang, Nan; Liu, Jianguo; Wang, Chenguang; Xu, Ying; Ma, Longlong
Abstract: Levulinic acid (LEV) has been identified as a key building block chemical produced entirely from biomass. Its derivatives can be used to synthesize a variety of value-added chemicals, such as 2-butanone, 2-methyltetrahydrofuran, and so on. LEV has carbonyl and carboxyl functional groups, which makes it flexible, diverse, and unique during drug synthesis. It also reduces the cost of drug synthesis and makes the reaction cleaner and, not the least, has untapped potential in the field of medicine. This article reviews the application of LEV in cancer treatment, medical materials, and other medical fields. Overall, LEV can be used in the following ways: (1) Used as a raw material to directly synthesize drugs; (2) Used to synthesize related derivatives, which can be more specifically used in drug synthesis, and derivatives can achieve the corresponding release of drugs, such as paclitaxel (PTX)- LEV, polymer-betulinic acid (BA)-LEV after amidation; (3) It can modify chemical reagents or act as linkers to connect pharmaceutical reagents with carriers to form pharmaceutical intermediates, a pharmaceutical intermediate skeleton, and so on. (4) It can acylate and esterify to form: acetylpropionate and levulinyl, the indole, pyridazine, and other medicinally active functional groups can be synthesized by a long chain, which can reduce the cost of drug synthesis and simplify the tedious synthesis steps. (5) To form the protective group of levulinic acid, the hydroxyl or carboxyl position is first protected, and then the protective group is removed after the corresponding reaction, in order to participate in drug synthesis.